1994
DOI: 10.1111/j.1476-5381.1994.tb13067.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 5‐lipoxygenase inhibitor and leukotriene antagonist (PF 5901) on antigen‐induced airway responses in neonatally immunized rabbits

Abstract: 1 The effect of a single intratracheal dose (10 mg) of phenoxymethyl] quinoline hydrochloride, a specific inhibitor of the 5-lipoxygenase pathway of arachidonic acid metabolism and a leukotriene D4 antagonist) on airway changes induced in response to Alternaria tenuis aerosol challenge was assessed in adult rabbits neonatally immunized. Leukotriene generation was determined in vivo by measuring leukotriene B4 (LTB4) levels in bronchoalveolar lavage (BAL) fluid and ex vivo by measuring calcium ionophore-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Since capsaicin (Herd et al, 1995) and the mixed 5-lipoxygenase/leukotriene D4 antagonist PF5901 (Herd et al, 1994) inhibited the development of airway hyperresponsiveness following antigen challenge in the rabbit, it has been suggested that a leukotriene-mediated activation of sensory C-fibres may contribute to antigen-induced airway hyperresponsiveness in this model. Interestingly, a range of PDE 4 inhibitors have been shown to inhibit electrical field stimulated excitatory nonadrenergic, non-cholinergic (eNANC) contraction of guineapig isolated bronchi in vitro whilst having no effect on contraction due to exogenous substance P (Qian et al, 1994;Spina et al, 1995).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since capsaicin (Herd et al, 1995) and the mixed 5-lipoxygenase/leukotriene D4 antagonist PF5901 (Herd et al, 1994) inhibited the development of airway hyperresponsiveness following antigen challenge in the rabbit, it has been suggested that a leukotriene-mediated activation of sensory C-fibres may contribute to antigen-induced airway hyperresponsiveness in this model. Interestingly, a range of PDE 4 inhibitors have been shown to inhibit electrical field stimulated excitatory nonadrenergic, non-cholinergic (eNANC) contraction of guineapig isolated bronchi in vitro whilst having no effect on contraction due to exogenous substance P (Qian et al, 1994;Spina et al, 1995).…”
Section: Discussionmentioning
confidence: 96%
“…Inhaled antigen in adult rabbits can elicit a similar sequence of events as seen in atopic asthmatics, including an acute bronchospasm and late phase obstruction (Larsen et al, 1987), airway hyperresponsiveness (AHR) (Bloom et al, 1988;Herd et al, 1994) and pulmonary eosinophil recruitment (Marsh et al, 1985;Herd et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…These responses are attenuated by clinically useful anti-asthma drugs [16], and the animals develop 2-6 fold increases in acute airway responsiveness, which resolves in one week [14,15,17,18]. Repeated measurements of lung function are readily made in the rabbit, and each animal may be used as its own control [18,19]. Taking this all together, led us to use the rabbit as the species of choice in our experiments investigating the effects of exposure to pollutant gases from birth.…”
Section: Technical Notementioning
confidence: 99%
“…They undergo early and late airways responses following antigen challenge [16][17][18], which is associated with airways oedema and inflammatory cell infiltration [19,20], are hyperresponsive to inhaled histamine and methacholine compared with naive rabbits [21,22], and exhibit airways hyperresponsiveness following challenge with either antigen or platelet-activating factor [18][19][20][21]. Repeated measurements of lung function are readily made in the rabbit, and each animal may be used as its own control [22][23][24]. We have, therefore, chosen the rabbit as the species in which to conduct our experiments investigating the effects of exposure to pollutant gases from birth.…”
mentioning
confidence: 99%